The Role of Strategic Grain Reserves in Enhancing Food Security in Zambia and Zimbabwe - World Bank (World Bank, Washington, DC, 2021)
Zambia and Zimbabwe have experienced food security emergencies of varying severity, mainly caused by drought and floods in some areas. Like several countries in Africa and elsewhere, the two countries have developed and used Strategic Grain Reserves (SGR) to cope with food emergencies and other functions to ensure the availability of food. Both countries have years of experience with SGR as a key component of their respective food security policies. At the center of this strategy is the availability and sufficient supply of white maize, as the single most important strategic crop. The study is organized into four parts as follows: Part 1 presents the introduction laying out the background, objectives, methodology and structure of the report; Parts 2 and 3 present separate country analysis for Zambia and Zimbabwe covering the overview of the food security situation, strategic grain reserve operations and management in relation to food emergencies, and recommendations to enhance the strategic grain management; and Part 4 presents the conclusion.